(untitled) - American Bible Society (United States of America, 2006)
A thoughtful exploration of the intriguing mysteries and unanswered questions of Scripture combines full-color illlustrations and photographs with commentary by renowned biblical scholars to offer a study of the story of Creation, the life and miracles of Jesus Christ, the Ark of the Covenant, ancient historical sites, and other key topics. Original.
Keywords: Bible